PERILAKU SEKSUAL REMAJA SMA DI PURWOKERTO DAN FAKTOR –FAKTOR YANG MEMPENGARUHINYA - Trisnawati, Yuli; Anasari, Tri; S., Artathi Eka (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
Based on the annual report of the Public Health Service in 2008 Banyumas mention visits from the distribution by age group in the case of some 28% of HIV and AIDS as much as 20% occurred at age 15-24 years, and 12% are in the teens caused by the heteroseksual. Nine sexual behaviors for the discovery of cases of sexually transmitted infections (STIs) by age group most widely found in the youth group is 40,74%. This study aims to determine the sexual behavior of adolescents and high school in Purwokerto factors-factors that influence it, namely the knowledge level of adolescents, adolescent attitudes toward sexuality, adolescent attitudes toward adolescent reproductive health services, the role of parent, peer behavior, and pornography. This type of research is survey with research descriptive analytical research design.Approach in this study is cross sectional. Research subjects were high school teenagers Purwokerto some 250 respondents. Data collection using questionnaires. Adolescent sexual behavior in high school Purwokerto majority (87,2%) no risk of unwanted pregnancy. There is a youth reproductive health knowledge, attitudes toward adolescent sexuality, adolescent attitudes toward reproductive health services, the role of parents, peers and the behavior of media access to pornography on sexual behavior of high school adolescents in Purwokerto. Variables studied, an influential effect on adolescent sexual behavior obtained significant variables with 95% confidence level associated with adolescent sexual behavior that is low knowledge with OR = 13,130. And the possible influence of the probability is 65%.   Key words: adolescent,sexual behavior, knowledge, attitudes, the role of parent.